2008
DOI: 10.1097/mcc.0b013e328306ef13
|View full text |Cite
|
Sign up to set email alerts
|

From rehabilitation to optimal function: role of clinical exercise therapy

Abstract: Physical therapy is a necessary component of the rehabilitation process. Although physical therapy often succeeds in restoration of the activities of daily life, patients are often unequipped to resume their pretrauma level of activity or functional capacity, including return to work or school. We opine that a vigorous program of physical training implemented soon after discharge from physical therapy is a logical and cost-effective extension of the continuum of rehabilitation after critical illness. Such exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 18 publications
0
18
0
3
Order By: Relevance
“…5,7 In one study, duration of mechanical duration and length of stay were not significantly decreased after use of an exercise protocol, but after-hospital costs of care were significantly lower, and quality of life was significantly improved. 9 Several issues complicate mobilization interventions, including timing of the interventions, widely variable practices, and the possibility that mobilization and related factors such as pain can aggravate the inflammatory process. Optimal timing for initiating mobilization is not known.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5,7 In one study, duration of mechanical duration and length of stay were not significantly decreased after use of an exercise protocol, but after-hospital costs of care were significantly lower, and quality of life was significantly improved. 9 Several issues complicate mobilization interventions, including timing of the interventions, widely variable practices, and the possibility that mobilization and related factors such as pain can aggravate the inflammatory process. Optimal timing for initiating mobilization is not known.…”
mentioning
confidence: 99%
“…13 Unstable physiological conditions in critically ill patients receiving mechanical ventilation may persist for days to weeks, delaying active mobility interventions and increasing disability. 9,14 If early passive exercise does not contribute to unstable physiological conditions, such exercise might be the most appropriate activity for critically ill patients in the early phase of illness 8 and can be used until a patient is ready to progress to more active interventions. However, limited empirical evidence supports the safety or efficacy of passive activity, particularly during periods of physiological instability.…”
mentioning
confidence: 99%
“…(11,15,20,21) Physical training in an ICU is a logical rehabilitation extension, and has been shown a key critical care component. (13) Exercises offer well-established physical and psychological benefits, and additionally reduce the oxidative stress and inflammation, due to increased anti-inflammatory cytokines production. (6) Previous studies have shown that in most times, after discharge from the hospital, patients with reduced body function will need a training schedule.…”
Section: Introductionmentioning
confidence: 99%
“…(10) All these factors associated contribute for prolonging the ICU stay, result in increased risks of complication, mortality and costs. (2,(11)(12)(13)(14)(15) Emotional disorders such as anxiety and depression increase the hospital stay, physical deficits, and may affect the function and consequently the one to seven years after the event patient's quality of life, entailing social impairment. (13,14,16) Early intervention is required to prevent both physical and psychological issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation